NMDA and Ampa receptors in synaptic membranes of cocaine and cocaine-prazosin treated rats - Ortiz, J. G.; Tirado Costacamps, A.; González Cabrera, S.; Rubio Dávila, M. M.; Berríos Cartagena, N.; Silva, W. I.; Jiménez Rivera, C. A. (Iatreia, 2005)
Sensitization, an increase in behavioral responses after repeated exposure to stimulants, occurs in the mesocorticolimbic pathway that includes the ventral tegmental area (VTA), the nucleus accumbens (NAc), hippocampus and the prefrontal cortex (PFC).